Leaf manganese accumulation and phosphorus-acquisition efficiency - Lambers, Hans; Hayes, Patrick E.; Laliberté, Etienne; Oliveira, Rafael S.; Turner, Benjamin L. (Trends in plant science, 2015)
•Plants that use a phosphorus (P)-mobilising strategy based on carboxylate release tend to have high leaf manganese concentrations ([Mn]).•This occurs because the carboxylates mobilise not only soil inorganic and organic P, but also a range of micronutrients, including Mn.•We propose that leaf [Mn] can be used to select for genotypes that are more efficient at acquiring P, when soil P availability is low.•Likewise, leaf [Mn] can be used to screen for belowground functional traits related to nutrient-acquisition strategies among species in low-P habitats. Plants that deploy a phosphorus (P)-mobilising strategy based on the release of carboxylates tend to have high leaf manganese concentrations ([Mn]). This occurs because the carboxylates mobilise not only soil inorganic and organic P, but also a range of micronutrients, including Mn. Concentrations of most other micronutrients increase to a small extent, but Mn accumulates to significant levels, even when plants grow in soil with low concentrations of exchangeable Mn availability. Here, we propose that leaf [Mn] can be used to select for genotypes that are more efficient at acquiring P when soil P availability is low. Likewise, leaf [Mn] can be used to screen for belowground functional traits related to nutrient-acquisition strategies among species in low-P habitats.